Remarks on Universal Health Coverage in Africa - Kim, Jim Yong (World Bank, Washington, DC, 2018)
Jim Yong Kim, President of the World Bank, argues that investing in universal health coverage (UHC) is an investment in the future. He mentioned three: First, UHC confronts poverty head on by protecting people from major disease outbreaks and from catastrophic health expenses; Second, UHC accelerates inclusive growth; and Third, UHC stimulates the health sector and creates jobs. The Bank is working with partners to identify the best ways to scale up interventions to improve nutrition and early child development, and to eliminate childhood stunting. He welcomes the government of Japan’s decision to support the annual production of the World Bank and World Health Organization global monitoring report on universal health coverage, with a strong focus on Africa.